Analisis Sistem Pengendalian Intern Piutang Semen Holcim Pada PT. Cahaya Niaga Nusantara Pontianak - B51106070, Misteri Faramita (Jurnal KIAFE, 2013)
This study entitled "Analysis of Internal Control System Receivables At Cement Holcim PT.Cahaya Niaga Nusantara Pontianak." Aims to determine the internal control system. Receivable at the Holcim cement accounts PT.Cahaya Niaga Nusantara Pontianak. Factors that led to the ineffectiveness of the internal control system at the Holcim cement receivable PT.Cahaya Niaga Nusantara Pontianak. Research conducted using descriptive method, which describes the real situation that happened to a PT. Cahaya Niaga Nusantara Pontianak. Techniques of data collection in this research; interviews, observation, research library. The data analysis technique used in this study is an analysis tool; organizational structure, internal control questionaires, flowchart and compliance testing. Based on the results of this study can be concluded that. Internal Control System at the receivable cement Holcim PT. Cahaya Niaga Nusantara Pontianak categorized effective, because the procedure concerning the accounts in accordance with company guidelines, but there are weaknesses in the section Credit Sales did not make the list offering price of all consumers. The factors that led to the ineffectiveness of the system of internal control accounts cement Holcim PT Cahaya Niaga Nusantara Pontianak. Light Commercial archipelago because the credit sale document examination is not always carried out by the Section supervision or control, not always held mutation felt it was time employees or territory transferred to another unit, the credit sale does not make a list of all consumers bid price, not to do periodic review of the list price of consumer demand. Keywords : Internal Control System, Accounts Receivable, Credit Sales, Inventory Cement Holcim.